LITERATURE REVIEW OF FACTORS AFFECTING DECISION MAKING: LEADERSHIP STYLE, PERSONALITY AND STRATEGY - Ricardo Ricardo (Dinasti International Journal of Education Management And Social Science, 2021)
Decision making is a process to produce several alternative choices that focus on expectations and efforts to achieve goals. Leadership is the quality of the relationship or interaction between a leader and followers in certain situations. The leader's role in making decisions is central and strategic. Of the various management functions, there is one management function, a study showed that the decision maker has its own style. Often there are several leadership styles possessed by a leader that are often used as patterns in decision making. Often a manager uses 2 or 3 styles of decision making. The strengths and weaknesses of decision making are determined by the style used by a leader or manager. The same information will be assessed and a decision made with a leadership style that is not aligned. This article reviews the factors that influence the decision-making process, namely leadership style and personality, a study of human resource management literature that will occur in this literature review article are: 1) Leadership style affect the decision-making process, 2) Personality affects the decision-making process, and 3) Strategy affects the decision-making process.